2019
DOI: 10.26434/chemrxiv.9981395.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Catalyst- and Silane- Controlled Enantioselective Hydrofunctionalization of Alkenes by TM-HAT and RPC Mechanism

Abstract: The catalytic enantioselective synthesis of tetrahydrofurans, found in the structures of many biologically active natural products, via a transition-metal-catalyzed hydrogen atom transfer (TM-HAT) and radical-polar crossover (RPC) mechanism is described. Hydroalkoxylation of non-conjugated alkenes proceeded efficiently with excellent enantioselectivity (up to 97:3 er) using a suitable chiral cobalt catalyst, <i>N</i>-fluoro-2,4,6-trimethylpyridinium tetrafluoroborate, and a diethylsilane. Surprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Co–H complex D reacts with the olefin substrates 1 through the HAT mechanism to afford branched alkylcobalt­(III) intermediate E regioselectively. The cationic cobalt­(III) complex C generated earlier goes back to the cobalt­(II) catalytic cycle via oxidation of alkylcobalt­(III) E to cationic alkylcobalt­(IV) complex F . , Finally, an S N 2-like displacement of F with silylated-BT G takes place to give the hydroamination product 3 and regenerate cobalt­(II) catalyst A .…”
mentioning
confidence: 99%
“…Co–H complex D reacts with the olefin substrates 1 through the HAT mechanism to afford branched alkylcobalt­(III) intermediate E regioselectively. The cationic cobalt­(III) complex C generated earlier goes back to the cobalt­(II) catalytic cycle via oxidation of alkylcobalt­(III) E to cationic alkylcobalt­(IV) complex F . , Finally, an S N 2-like displacement of F with silylated-BT G takes place to give the hydroamination product 3 and regenerate cobalt­(II) catalyst A .…”
mentioning
confidence: 99%
“…This discouraging selectivity exposed the inherent limitation of MHAT reactions: substrate dependent stereoselectivity in almost all cases. 58 Solvent screens were possible using cobalt catalysis, 59 but Mn and Fe catalysts typically required an alcoholic solvent to function. Our lab found that these catalysts required alcohol because the standard reductant, PhSiH3, performed poorly compared to its mono-alcoholysis product, isopropoxy(phenyl)silane, a highly efficient reductant that functions in numerous solvents.…”
Section: X-ray Data For Bilobalide Intermediates (-)-14 Giese Reactionmentioning
confidence: 99%
“…Previously, our laboratory reported that the addition of an N -fluoropyridinium salt to the TM-HAT cobalt catalysis gave rise to a radical-polar crossover (RPC) mechanism that generated a formal cationic species, enabling the functionalization of alkenes with a nucleophile under nearly neutral conditions . Thus, our original plan for hydrothiolation was to use a thiol group as a nucleophile.…”
mentioning
confidence: 99%